2018
DOI: 10.1021/acs.jpcb.8b04388
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interactions between Trimethylamine N-Oxide (TMAO), Urea, and Water

Abstract: Trimethylamine N-oxide (TMAO) and urea are two important osmolytes with their main significance to the biophysical field being in how they uniquely interact with proteins. Urea is a strong protein destabilizing agent, whereas TMAO is known to counteract urea's deleterious effects. The exact mechanisms by which TMAO stabilizes and urea destabilizes folded proteins continue to be debated in the literature. Although recent evidence has suggested that urea binds directly to amino acid side chains to make protein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…TMAO has beneficial as well as harmful effects. On the protective side, it serves as an osmolyte [6,36] that stabilizes protein structures against destabilizing forces, such as urea, and maintains the volume of intestinal cells under osmotic and hydrostatic stresses [34,37,54]. It supports oxidative phosphorylation as an electron acceptor for the Enterobacteriaceae flora that grows in the anaerobic intestine, thereby maintaining a healthy symbiotic balance in the microenvironment [29].…”
Section: Microbiome Alters the Dietary Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…TMAO has beneficial as well as harmful effects. On the protective side, it serves as an osmolyte [6,36] that stabilizes protein structures against destabilizing forces, such as urea, and maintains the volume of intestinal cells under osmotic and hydrostatic stresses [34,37,54]. It supports oxidative phosphorylation as an electron acceptor for the Enterobacteriaceae flora that grows in the anaerobic intestine, thereby maintaining a healthy symbiotic balance in the microenvironment [29].…”
Section: Microbiome Alters the Dietary Compositionmentioning
confidence: 99%
“…TMAO may critically benefit renal function in systemic inflammatory diseases by being a “chemical chaperone” to enhance the folding and stability of proteins, and an osmolyte to maintain cellular fluid balance [6,36]. It accumulates in the endoplasmic reticulum to promote protein folding, thereby inhibiting ER stress and attenuating the formation of intracellular aggregates [141].…”
Section: Tmao Can Harm or Protect The Renal Function Of Ra Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full geometry optimizations and corresponding harmonic frequency calculations were performed on TMAO, guanidinium cation, and water using common DFT methods, specifically the M06‐2X [ 69 ] and ωB97XD functionals, [ 70 ] and using Dunning's aug‐cc‐pVDZ and aug‐cc‐pVTZ basis sets. [ 71–73 ] DFT methods have been previously used to study similar biomolecules, [ 28,39,68,74–78 ] with M06‐2X specifically being shown to account for the dispersion that affects the hydrogen bonding interactions occurring in aqueous solvation shells. [ 79–82 ] Lorentzian‐type functions for each normal mode were combined in order to create simulated Raman spectra.…”
Section: Methodsmentioning
confidence: 99%
“…[ 60,64–67 ] More recently, we showed that TMAO preferentially interacts with urea, which induces a blue shift (shift to higher energy) in the wavenumbers of the H‐N‐H symmetric bending mode of urea. [ 15,68 ]…”
Section: Introductionmentioning
confidence: 99%